2004
DOI: 10.1111/j.0031-9317.2004.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Flowering genes in Metrosideros fit a broad herbaceous model encompassing Arabidopsis and Antirrhinum

Abstract: Molecular studies were conducted on Metrosideros excelsa to determine if the current genetic models for flowering with regard to inflorescence and floral meristem identity genes in annual plants were applicable to a woody perennial. MEL, MESAP1 and METFL1, the fragments of LEAFY (LFY), APETALA1 (AP1) and TERMINAL FLOWER1 (TFL1) equivalents, respectively, were isolated from M. excelsa. Temporal expression patterns showed that MEL and MESAP1 exhibited a bimodal pattern of expression. Expression exhibited during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Similar bimodal expression and developmental events have been observed in Actinidia (Walton et al 2001), Vitis (Carmona et al 2002), Populus (Cseke and Podila 2004), and Metrosideros (Sreekantan et al 2004) although in these cases the dormant period occurred during winter. Expression of the StLFY in Sophora was relatively low at the time of inflorescence initiation (Song et al 2008), although Walton et al (2001) and Sreekantan et al (2004) found LFY homologues to be upregulated at this time.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar bimodal expression and developmental events have been observed in Actinidia (Walton et al 2001), Vitis (Carmona et al 2002), Populus (Cseke and Podila 2004), and Metrosideros (Sreekantan et al 2004) although in these cases the dormant period occurred during winter. Expression of the StLFY in Sophora was relatively low at the time of inflorescence initiation (Song et al 2008), although Walton et al (2001) and Sreekantan et al (2004) found LFY homologues to be upregulated at this time.…”
Section: Discussionsupporting
confidence: 69%
“…Floral induction occurs in autumn (Sreekantan et al 2001) and while floral primordia are microscopically evident by May, organ differentiation does not occur until September. Sreekantan et al (2004) showed elevated MESAP1 and MEL expression in buds during cymule formation and again later during organ differentiation. Ambient (winter) conditions were shown by Henriod et al (2000Henriod et al ( , 2003 to be conducive to full floral development.…”
Section: Discussionmentioning
confidence: 99%
“…Two distinct TFL1 homologs control pea (Pisum sativum) vegetative and reproductive phase duration: The LATE FLOWERING gene maintains shoot apical meristem indeterminacy, and DE-TERMINATE (DET) maintains inflorescence meristem indeterminacy (Foucher et al, 2003). TFL1 homologs with conserved function have now been identified in many eudicotyledonous (Amaya et al, 1999;Pillitteri et al, 2004;Sreekantan et al, 2004;Kotoda and Wada, 2005;Boss et al, 2006;Kim et al, 2006) and monocotyledonous plants (Jensen et al, 2001;Nakagawa et al, 2002;Zhang et al, 2005). The Arabidopsis TFL1 protein has recently been shown to be a mobile signal that moves from its localized transcriptional domain in the central region of the inflorescence meristem to the entire meristem, where it exerts its activity.…”
mentioning
confidence: 99%
“…In general, the structure and function of TFL1-related proteins are greatly conserved (Kato et al, 1998;Pnueli et al, 1998;Jensen et al, 2001;Nakagawa et al, 2002;Carmel-Goren et al, 2003;Sreekantan et al, 2004;Chardon and Damerval, 2005;Esumi et al, 2005;Kotoda and Wada, 2005;Zhang et al, 2005;Boss et al, 2006;Guo et al, 2006;Kim et al, 2006;Argiriou et al, 2008;Datta et al, 2008;Igasaki et al, 2008;Elitzur et al, 2009;Hiroyuki et al, 2009;Mimida et al, 2009). However, there is evidence for diversification and specification of the function of different TFL1 family members.…”
mentioning
confidence: 99%